Ammonia Excretion in an Osmoregulatory Syncytium Is Facilitated by AeAmt2, a Novel Ammonia Transporter in Aedes aegypti Larvae - Durant, Andrea C.; Donini, Andrew (Frontiers in Physiology, 2018)
The larvae of the mosquito Aedes aegypti inhabit ammonia rich septic tanks in tropical regions of the world that make extensive use of these systems, explaining the prevalence of disease during dry seasons. Since ammonia (NH3/NH4+) is toxic to animals, an understanding of the physiological mechanisms of ammonia excretion permitting the survival of A. aegypti larvae in high ammonia environments is important. We have characterized a novel ammonia transporter, AeAmt2, belonging to the Amt/MEP/Rh family of ammonia transporters. Based on the amino acid sequence, the predicted topology of AeAmt2 consists of 11 transmembrane helices with an extracellular N-terminus and a cytoplasmic C-terminus region. Alignment of the predicted AeAmt2 amino acid sequence with other Amt/MEP proteins from plants, bacteria, and yeast highlights the presence of conserved residues characteristic of ammonia conducting channels in this protein. AeAmt2 is expressed in the ionoregulatory anal papillae of A. aegypti larvae where it is localized to the apical membrane of the epithelium. dsRNA-mediated knockdown of AeAmt2 results in a significant decrease in NH4+ efflux from the anal papillae, suggesting a key role in facilitating ammonia excretion. The effect of high environmental ammonia (HEA) on expression of AeAmt2, along with previously characterized AeAmt1, AeRh50-1, and AeRh50-2 in the anal papillae was investigated. We show that changes in expression of ammonia transporters occur in response to acute and chronic exposure to HEA, which reflects the importance of these transporters in the physiology of life in high ammonia habitats.